GAYA BAHASA DALAM NOVEL AIR MATA TUHAN KARYA AGUK IRAWAN M.N. - Sumadi Sumadi (EDU-KATA, 2019)
The purpose of this research is to describe the style of language used in the novel Air Mata Tuhan by Aguk Irawan M.N.; This research is a descriptive qualitative. Based on the results of the study concluded that there are some elements of style in the novel Air Mata Tuhan by Aguk Irawan M.N., including; hyperbole, personification, perumpaman, metaphor, allegory, allusion, simile, associations, epithet, eponym, pars pro toto, euphemism, anaphora, epizeukis, litotes, paradox, parallelism, climax, and reps.